Developing reactors for electrifying bio-methanation: a perspective from bio-electrochemistry. Issue 5 (11th February 2022) - Jayathilake, Buddhinie S.; Chandrasekaran, Swetha; Freyman, Megan C.; Deutzmann, Jörg S.; Kracke, Frauke; Spormann, Alfred M.; Huang, Zhe; Tao, Ling; Pang, Simon H.; Baker, Sarah E.
Abstract : Next-generation electro-bioreactors will require development of novel reactor-tailored components to improve reactor productivity while maintaining high energy efficiency and biocompatible reactor conditions. Abstract : The integration of microbial synthesis with renewable electricity is an emerging route for both CO2 utilization and seasonal energy storage in the form of stored bio-electrofuels. The major benefits of electrifying bioreactors include: using highly selective bio-catalysts for CO2 conversion under mild reaction conditions; decoupling the production of more facile electrochemical intermediates, such as hydrogen, at the electrode from the production of bio-catalyzed multi-electron and/or carbon products, such as methane or acetate; using microbes as robust and self-regenerating catalysts enabling higher efficiency and durability in CO2 conversion systems compared to inorganic catalysis. In this Perspective, we propose research aimed at developing electro-bioreactor components that will increase the productivity of the reactor while maintaining high energy efficiency and biocompatible reaction conditions to fully realize the benefits of electrified bioreactors. These developments include: flow reactors with tailored 3D electrodes to optimally use the reactor volume, electrocatalysts designed for peak performance in neutral pH electrolytes, high conductivity microbial media, and new membrane separator materials with high ion conductivity and low gas permeability. Production of methane via a hybrid electrical-biological approach is taken as a case study to motivate these developments. Finally, an iterative design–manufacture–test cycle, enabled by additive manufacturing and 3D printing technologies, is proposed to rapidly prototype components prior to large-scale manufacturing.